TINGKAT PROFITABILITAS EFEK LOAN TO DEPOSIT RATIO (LDR) DAN PERTUMBUHAN DANA PIHAK KETIGA PADA PERBANKAN BUMN DI BURSA EFEK INDONESIA - Jannati Tangngisalu (Jurnal Manajemen, Bisnis dan Organisasi (JUMBO), 2020)
The level of profitability of the banking BUMN listed in Indonesia Stock Exchange is an issue that is still interesting to study as a result of the uncertainty and competition of private banks in collecting third party funds from the public. This study aims to determine the effect of the Loan to Deposit Ratio (LDR) and the growth of third party funds on profitability of the banking BUMN listed in Indonesia Stock Exchange for the period 2008 to 2017. The population used in this study is all state-owned banks in the IDX period 2008 until 2017. The sample selection in this study uses saturated sampling. The sample used in this study were 4 BUMN banks in the period 2008 to 2017. Data used in this study used secondary data. The testing method used in this study is using multiple regression analysis methods. The results showed that the LDR and DPK significantly influence profitability. While the most dominant variable affecting profitability in this study is liquidity (Loan to Deposit Ratio)